Environmental management in design : lessons from Volvo and Hewlett-Packard for the Department of Defense - Resetar, Susan A., 1961-; Camm, Frank A., 1949-; Drezner, Jeffrey A.; Rand Corporation; United States. Department of Defense. Office of the Secretary of Defense; National Defense Research Institute (U.S.) (Santa Monica, CA : Rand, 1998)
The Defense Department, seeking methods to hold the line on environmental costs, can look to corporations in the private sector for novel approaches to environmental management. Corporations have learned that, if environmental issues are considered in the design stage, the payoffs over the life of the product or system can be large. The authors of this report concentrate on two corporations -- Volvo and Hewlett-Packard -- to identify the key factors that led to successful implementation of a design-for-environment program. The report shows, by drawing on the experience of Volvo, Hewlett-Packard, and other industry leaders, how DoD can incorporate pollution prevention into design activities of weapon systems without any loss of capability and with a potential for enormous savings.
Introduction -- Environmental Issues in Weapon Systems Acquisition -- What Is Design-For-Environment? -- No Silver Bullets: Elements of a Comprehensive Process -- Conclusions and Recommendations -- Appendix A: Volvo Case Study: Driving Toward Green -- Appendix B: Hewlett-Packard Case Study: Product Stewardship: Green Computes -- Bibliography.
"Prepared for the Office of the Secretary of Defense ; National Defense Research Institute."
Includes bibliographical references (pages 143-150).
"MR-1009-OSD."
Print version record.
eBooks on EBSCOhost
Keywords: United States. -- Department of Defense -- Procurement -- Environmental aspects; Volvo, Aktiebolaget -- Management -- Environmental aspects; Hewlett-Packard Company -- Management -- Environmental aspects; Hewlett-Packard Company; United States. -- Department of Defense; Volvo, Aktiebolaget; United States -- Armed Forces -- Weapons systems -- Design and construction -- Environmental aspects; Defense contracts -- Environmental aspects -- United States; Environmental management -- Case studies; Contrats de la défense -- Aspect de l'environnement -- États-Unis.; Environnement -- Gestion -- Études de cas; TECHNOLOGY & ENGINEERING -- Military Science; HISTORY -- Military -- Other; Armed Forces -- Procurement -- Environmental aspects; Defense contracts -- Environmental aspects; Environmental management; Management -- Environmental aspects; United States; Case studies